The pattern and socio-cultural determinants of intimate partner violence in a Nigerian rural community - Israel C. Ikekwuibe; Collins E.M. Okoror (AOSIS, 2021)
Background: Intimate partner violence (IPV) refers to a violation of women's reproductive rights as it impacts on their sexual and reproductive health autonomy. Aim: In this study, we aimed at assessing the pattern of IPV and the socio-cultural determinants and predictors of partner violence in a rural community setting where the bulk of the abuse prevails. Setting: This study was conducted in a rural community in Southern Nigeria. Methods: This study employed a mixed method comprising seven focus group discussions (FGDs) and quantitative components. The cross-sectional survey was conducted amongst 209 ever married or cohabited females in 2018 using the World Health Organization (WHO) multi-country survey questionnaire adapted to the study objectives. Data analysis was conducted by using IBM SPSS v21.0. The level of significance was set at p 0.05. Results: The overall IPV prevalence was 79.4%. The prevalence of partner's controlling behaviour, emotional IPV, physical IPV and sexual IPV was 62.6%, 55.98%, 49.3% and 2.6%, respectively. Membership of an interest group was protective against IPV (OR = 0.430, 95% CI = 0.193-0.957) whilst the belief that a good wife obeys her partner even if she disagrees (OR = 9.201, 95% CI = 1.299-65.194) and the belief that it is the wife's obligation to have sex with the husband even if she doesn't feel like (OR = 2.356, 95% CI = 1.049-5.288) were risk factors. Conclusion: The burden of IPV in the studied rural community is enormous. There should be public enlightenment to desensitise people regarding the erroneous views that encourage partner violence. We encourage women to become a part of social groups that can enhance their education and empowerment.